Phase II study of reintroduction of oxaliplatin for advanced colorectal cancer in patients previously treated with oxaliplatin and irinotecan: RE-OPEN study - Suenaga M; Mizunuma N; Matsusaka S; Shinozaki E; Ozaka M; Ogura M; Yamaguchi T (Dove Medical Press, 2015)
Mitsukuni Suenaga,1 Nobuyuki Mizunuma,1 Satoshi Matsusaka,1 Eiji Shinozaki,1 Masato Ozaka,1 Mariko Ogura,1 Toshiharu Yamaguchi21Department of Gastroenterology, 2Department of Gastroenterological Surgery, Cancer Institute Hospital of Japanese Foundation for Cancer Research, Tokyo, JapanBackground: The effectiveness of reintroducing oxaliplatin in patients with metastatic colorectal cancer refractory to standard chemotherapy has not been verified. We performed a single-arm, open-label, Phase II study to evaluate the safety and efficacy of reintroducing oxaliplatin. Methods: Eligible patients had received prior chemotherapy including oxaliplatin and irinotecan that achieved a response or stable disease followed by confirmed disease progression ≥6 months previously during prior oxaliplatin-based therapy. The primary endpoint was the disease control rate (DCR) after 12 weeks of treatment starting. The DCR was defined as the sum of patients with complete response, partial response, and stable disease. Results: Thirty-three patients were enrolled. The median age was 62 (range: 35–77) years and the male/female ratio was 19/14. Eastern Cooperative Oncology Group performance status was 0 in 84.8%. Fourteen primary tumors were in the colon and 19 were in the rectum. All patients received modified FOLFOX6 as the protocol treatment. After 12 weeks of treatment starting, the DCR was 39.4% (95% confidence interval 21.8–57.0) and the response rate (complete response and partial response) was 6.1%. The median number of chemotherapy cycles was five and the median total dose of oxaliplatin was 425 mg/m2. Median progression-free survival time was 98 days and median overall survival was 300 days. The incidence of grade ≥1 and grade ≥3 allergic reactions was 28.1% and 3.1%, respectively. The incidence of grade ≥1 and grade ≥3 peripheral sensory neuropathy was 53.1% and 0%, respectively. There were no other severe adverse events and no treatment-related deaths.Conclusion: Reintroducing oxaliplatin can be both safe and effective. This may be a salvage option for patients with metastatic colorectal cancer who achieved a response or stable disease with prior oxaliplatin-based therapy followed by disease progression ≥6 months previously during prior oxaliplatin-based therapy.Keywords: reintroduction, oxaliplatin, FOLFOX, advanced colorectal cancer, salvage-line